Penilaian tingkat keberhasilan perawatan ortodonti dengan piranti lepasan berdasarkan parameter intermolar distance, inter dm2 distance, dan koreksi anterior crowding (Kajian Pada Pasien Anak Usia 7 – 10 Tahun di RSGM-P Universitas Trisakti Tahun 2017 - - Asima Hutapea, Frida; Halim, Himawan (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Removable orthodontic appliance is one of the solutions of malocclusion problems in Indonesia. This appliance can treat mild to moderate dental malocclusion, such as Class I Angle, and can be removed by patients under the supervision of a dentist. Assessment of the success rate of removable orthodontic treatment can be performed using intermolar and inter dm2 distance measurements with anterior crowding correction. Objective: To determine orthodontic treatment success rate using removable appliance based on intermolar and inter dm2 distance measurement with anterior crowding correction in children aged 7-10 years at RSGM-P Trisakti University 2017-2019. Methods: The study was observational analytic to perform measurements of anterior crowding, intermolar, and inter dm2 distance on 26 pairs of the study model were selected using a random sampling method. Results: 19 patients have an increase in width at intermolar distance maxillary parameter and 22 patients at the mandibular (range 0.5 - 7 mm). 24 patients have an increase in width at inter dm2 distance maxillary parameter and 23 patients at mandibular (range 0.5 - 4 mm). All patients have an intermolar distance that exceeds the Pont prediction before orthodontic treatment. Conclusion: There were significant differences in maxillary and mandibular intermolar and inter dm2 distance parameters measurement of the study model before and after orthodontic treatment (p <0.05). There was no significant difference in anterior crowding parameter measurement of the study model before and after orthodontic treatment (p> 0.05).